Apprentices and experts on basketball incidental learning. Two diferent cognitive processes - Camacho-Lazarraga, P.; Calvo-Lluch, Á. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The aim of the study is to review and systematically evaluate the literature related to the strategies of incidental teaching in young athletes and experts in the learning of skills related to basketball, in order to analyze the underlying effects between two different cognitive processes in learning and performance. During the search process, the Web of Science, Scopus, SportDiscus and PsycInfo databases were consulted, in addition to other research sources, and 26 studies were finally selected. The results indicate that, in general, reducing the amount of information processed by players produces a positive effect on learning and performance. Athletes with low experience in the mastery of a skill benefit from a teaching style that favors incidental learning. Expert athletes rely on more intuitive processing than novice players.